El més enllà en sant Vicent Ferrer, Francesc Eiximenis i sor Isabel de Villena. Els llimbs dels patriarques. - VILARDELL, ALBERT TOLDRÀ I. (Scripta, 2019)
The limbo of patriachs or Sine of Abraham is a space of the afterlife with vestibular disposition, where the personages of the old Testament wait before redemption. Christ goes down when dies, rescues them and closes this space. In the Catalan textual and iconographic tradition, while Christ is in limbo, he shows the patriarchs his own body still on the cross, and all together visit Mary.